Legal Analysis of Rejection of Life Insurance Claims By Insurance Companies Based on the Principles of Good Faith and Consumer Protection - Laila Rizqillah; Amanda Putri Fajrin; Salwa Khairina Azzahra; Nabila Hilmy Khairunnisa Hasibuan; Nadiatul Maghfirah (Jurnal Sahabat ISNU SU, 2024)
One of the most common causes of disputes between insured and insurance companies is the rejection of life insurance claims. Life insurance is essentially a contract that offers protection against the possibility of death or other perils stated in the policy. However, in reality, many insurance companies refuse to pay claims for various reasons, including policy limitations, discrepancnies in the coverage data, alleged violations of the principle of absolute good faith, or other administrative reasons. As parties entitled to insurance benefits, this situation often results in legal confusion for the insured and their heirs. This study aims to investigate the legal justification for life insurance claim rejections by insurance companies, examine the legal protections for the insured, and investigate the legal consequences of claim rejections that violate legal requirements. The research methodology used is normative legal research using statutory, conceptual, and case study approaches. The findings indicate that insurance companies can only reject claims if there is a strong legal basis in accordance with the policy provisions and relevant laws and regulations. Unilateral rejection of claims without a valid reason can be considered a breach of contract (default) or possibly an illegal act requiring compensation. Alternative Dispute Resolution Institutions in the Financial Services Sector, insurance companies' internal dispute resolution procedures, or court litigation can all be used to seek legal protection for insured parties. Therefore, to provide legal certainty and preserve the rights of insured parties, it is crucial to increase transparency in insurance claims procedures and strengthen oversight by the Financial Services Authority (OJK).